Peningkatan Hasil Belajar Siswa pada Materi Dinamika Gerak Partikel Dengan Menerapkan Model Pembelajaran Project Based Learning - Vina Serevina; Dewi Muliyati (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2015)
AbstractThis study aims to determine improving student learning outcomes in learning physics by applying the Project Based Learning Model with Planning phases (planning), Creating (creation or implementation), and processing. The object of this research is the students of class X MIPA 3 SMA Negeri 68 Jakarta with 37 students. The research method used is Classroom Action Research with Model Chemish & Mc.Taggart which are the phases: planning (planning), action (acting), observation (observing) and reflection (reflecting), in collaboration with the teacher of the class. The study was conducted by two cycles, the first cycle consisted of two meetings, in the second cycle two meetings, too. Data collection been done from the results of Physics of student learning, interviews and field notes. The results of this research with the achievements in materials physics of Dynamics Motion Particle, respectively in the first cycle: Average of Affective score: Scientific Attitude and motivation of students is not optimal, Average of Cognitive score of Students: 43.7 and Average of Psychomotor score of student: 45.3. Results in cycle 1 is still below The Minimum Criteria Score for completeness (KKM) in Physics of SMAN 68 Jakarta = 75. In Cycle II: Average Affective score of students: Attitudes Scientific is high score with the student response was quick and student motivation was optimal with high residual enthusiasm, Average Cognitive score of student: 84.5 and Average Psychomotor score of students: 83.5. The result of this research showed that by applying the Project Based Learning Model can improve student learning outcomes (affective, cognitive and Psychomotor).Keywords: Project Based Learning Model, Result Study of Physics.AbstrakPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar siswa dalam pembelajaran fisika dengan menerapkan model pembelajaran Project Based Learning dengan tahapan Planning (perencanaan), Creating (mencipta atau implementasi), dan Processing (pengolahan). Objek penelitian adalah siswa kelas X IPA 3 SMA Negeri 68 Jakarta sebanyak 37 siswa. Metode penelitian yang dipakai adalah metode penelitian tindakan kelas Model Kemis & Mc.Taggart dngan tahap: perencanaan (planning), tindakan (acting), pengamatan (observing), dan refleksi (reflecting), yang berkolaborasi dengan guru pengajar di kelas. Penelitian dilakukan sebanyak dua siklus, pada siklus pertama terdiri dari dua kali pertemuan, pada siklus kedua dua kali pertemuan. Metode pengumpulan data dengan hasil belajar siswa, wawancara dan catatan lapangan. Hasil penelitian ini dengan capaian pada materi Fisika Dinamika Gerak Partikel, secara berturut-turut pada siklus I: Nilai Afektif Rata-rata: Sikap Ilmiah dan Motivasi siswa belum optimal, Nilai Kognitif Siswa rata-rata: 43.7 dan Nilai Naskah diterbitkan: 30 Juni 2015 DOI: doi.org/10.21009/1.01109 JPPPF - Jurnal Penelitian & Pengembangan Pendidikan Fisika Volume 1 Nomor 1, Juni 2015p-ISSN: 2461-0933 | e-ISSN: 2461-1433 Halaman 62 e-Jurnal: http://jpppf.fisika-unj.ac.id Psikomotor siswa rata-rata: 45,3. Hasil pada siklus 1 masih di bawah Nilai Kriteria Ketuntasan Minimal (KKM) Fisika SMAN 68 Jakarta = 75. Pada Siklus II: Nilai Afektif Rata-rata: Sikap Ilmiah yang tinggi dengan respon yang siswa cepat dan Motivasi siswa sudah optimal dengan antusiasme sisa yang tinggi, Nilai Kognitif Siswa rata-rata Hasil Test: 84.5 dan Nilai Psikomotor siswa rata-rata: 83.5. Hasil penelitian ini menunjukkan bahwa dengan menerapkan model pembelajaran Project Based Learning dapat meningkatkan hasil belajar siswa (aspek afektif, kognitif dan Psikomotornya).Kata-kata kunci : Model pembelajaran Project Based Learning, Hasil Belajar Fisika.